How Digital Content Marketing, Fashion Involvement, and Trust Influence Online Purchase Intention on TikTok: The Mediating Role of eWOM - Fahmiatul Ilmiyah; Dimas Negoro (Manunggal Halim Jaya, 2026)
This study aims to examine the relationship between Digital Content Marketing, Fashion Involvement, and Trust on Online Purchase Intention, with Electronic Word of Mouth (eWOM) acting as a mediating variable on the TikTok platform. The research focuses on active TikTok users who regularly engage in fashion-related purchases, providing insight into how digital engagement and consumer perceptions influence purchasing behavior in social commerce environments. A total of 200 potential respondents were targeted, and 130 valid responses were successfully collected using purposive sampling techniques. All respondents had experience purchasing fashion products at least once per month, ensuring the relevance of their consumption behavior to the research context. A quantitative approach was employed, utilizing Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1 software to analyze the proposed relationships. The findings reveal that Digital Content Marketing, Fashion Involvement, and Trust each have a positive and significant effect on Electronic Word of Mouth. This indicates that engaging digital content, strong personal involvement in fashion, and consumer trust collectively encourage users to share opinions, reviews, and recommendations online. Furthermore, Electronic Word of Mouth demonstrates a significant direct effect on Online Purchase Intention, confirming its critical role in shaping consumers’ buying decisions. Importantly, the results also show that Electronic Word of Mouth effectively mediates the influence of Digital Content Marketing, Fashion Involvement, and Trust on Online Purchase Intention. This suggests that while these antecedent variables directly enhance consumers’ perceptions, their impact on purchase intention is substantially strengthened through eWOM mechanisms. Overall, the study highlights the strategic importance of fostering credible digital content, building consumer trust, and encouraging positive eWOM to stimulate online purchase intentions within social media–based fashion markets.